Gastrointestinal adverse events associated with GLP-1 receptor agonists in metabolic dysfunction-associated steatotic liver disease (MASLD): a systematic review and meta-analysis - Huang, Xiaoyan; Wu, Miaohui; Huang, Baoliang; Zhang, Yi (Frontiers in Medicine, 2025)
BackgroundMetabolic dysfunction-associated steatotic liver disease, a prevalent chronic liver condition, can cause severe complications like hepatitis, cirrhosis, and hepatocellular carcinoma. In recent years, glucagon-like peptide-1 receptor agonists (GLP - 1RA) have shown unique therapeutic advantages and may become a preferred treatment for it. This meta-analysis aims to systematically examine GLP-1RA associated adverse events, providing a basis for guiding patient clinical management.MethodsWe conducted a search for randomized controlled trials (RCTs) investigating the therapeutic effects of GLP-1RA in the treatment of metabolic dysfunction-associated steatotic liver disease across four databases: PubMed, Embase, Web of Science, and Cochrane Library. The search period extended from the inception of each database until December 2023. Information pertaining to various adverse events was collected as outcome measures. Statistical analysis of the results and assessment of bias risk were conducted utilizing Review Manager (version 5.4.1) software.ResultsAn analysis of 10 studies encompassing 960 participants revealed a significantly higher overall incidence of adverse events in the GLP-1RA group compared to the control group (OR: 2.40 [1.10, 5.26], P = 0.03). Subgroup analysis based on treatment duration demonstrated a higher rate of adverse events in the GLP-1RA group during follow-ups of less than 30 weeks (P = 0.0005, OR: 3.58 [1.75, 7.32]), but no statistical difference was observed between the two groups in follow-ups exceeding 30 weeks. There was no statistically significant difference between the two groups in adverse events leading to discontinuation (P = 0.29, OR: 1.47 [0.72, 2.98]). However, a notable difference was observed in gastrointestinal adverse events (P < 0.00001, OR: 4.83 [3.36, 6.95]).ConclusionGLP-1RA exhibits an overall higher incidence of adverse events in the treatment of metabolic dysfunction-associated steatotic liver disease, particularly in the gastrointestinal domain. Short-term use of GLP-1RA may be associated with a greater occurrence of adverse events, underscoring the importance of educating patients on preventive measures and establishing tolerance. However, there was no statistically significant difference between the two groups in severe adverse events and adverse events leading to discontinuation, confirming the safety profile of GLP-1RA application.